The Mental Health among Disabled in Baghdad (Journal Of Educational and Psychological Researches, 2017)
The aims of this research are : 1. To measure mental health among disabled in Baghdad. 2. To identify the statistical differences in mental health among disabled in Baghdad according to gender. 3. To identify the statistical differences in mental health among disabled in Baghdad according to age. The scale of mental health (Aljbori&abdulhussin,2015) was adopted by the researcher, A purposely sample were selected of (60) disabled at Iraqi Alliance of Disabilitiv (IAD) in academic year 2015 to 2016. Where data have analyzed by SPSS. The results found. 1. The disabled characterized with good level of mental heath. 2. There was no significant differences between ganders 3. There are no significant differences between age. Results and recommendation for research are discussed.